Topiramate and Pregabalin in Lumbar Radicular Pain. Is Topiramate a better option? - Asim Ishfaq , Javaria Ashraf , Aimen Haider, Asim Ishfaq , Javaria Ashraf , Aimen Haider (Journal of Rawalpindi Medical College, 2020)
Objective: To compare the efficacy of two anticonvulsant drugs topiramate and pregabalin on lumbar radicular pain and to find out whether topiramate is a better option or not. Study design: Experimental study. Place and Duration: Department of Neurosurgery, Combined Military Hospital Lahore. January 2020 - March 2020. Patients and Methods: 60 patients of both gender divided in two groups of 30 each were included. Patients were assessed based on subjective impairment scale of oswestry disability index. Maximum score was calculated in percentage with higher score pointing to greater disability. Both drugs were given in low starting once daily dose, 75 mg for pregabalin and 25 mg for topiramate for two weeks followed by twice daily dose for two more weeks in patients not getting pain relief. Results: Male to female ratio of 4:1 in both groups. Age range of 27-77 years (41.5+12.45) for pregabalin and 22-74 years (41.6+14.6) for topiramate group. Baseline demographics and pre drug pain measurement index were identical amongst two groups. Oswestry disability index was 49.2+18.3 pre drug and post drug 41+16.4 for pregabalin (p<0.01). For topiramate it was 43.6+37.9 pre drug and 37.9+17.3 post drug (p <0.01). Conclusion: Both pregabalin and topiramate are effective in radicular pain management, and topiramate is not better but still a viable option as an alternative to pregabalin.